Moon craving : a children of the moon novel - Monroe, Lucy, 1967- (Monroe, Lucy, 1967- Children of the moon, 2010)
When the king orders him to marry an Englishwoman, Talorc, the laird of the Sinclair clan and leader of his werewolf pack, quickly falls in love with his bride, but their happiness is threatened when she discovers his true nature.